Extreme Anisotropies in Deep Layers of an Exploding Star: Overabundance of Cr in the Northeastern Jet of Cassiopeia A - Vincenzo Sapienza; Marco Miceli; Masaomi Ono; Shigehiro Nagataki; Takashi Yoshida; Emanuele Greco; Salvatore Orlando; Fabrizio Bocchino (The Astrophysical Journal Letters)
Core-collapse supernovae (CCSNe) drive nucleosynthesis under extreme thermodynamic conditions, and complex mechanisms are at work prompting the transport of heavy elements from deep stellar interiors into outer layers. We present spatially resolved X-ray spectroscopy of the northeastern (NE) jet of Cassiopeia A (Cas A) using the archival 1 Ms Chandra/ACIS observations, and focusing on three fingers of the jet. We report the highest Cr/Fe mass ratio (Cr/Fe ∼0.14) ever observed in Cas A, localized in a compact region within the southernmost finger in the NE jet. Comparisons with nucleosynthesis models indicate that the NE jet originated approximately at the boundary separating the complete Si-burning layer from the incomplete Si-burning layer. We also find that mixing from different layers is needed to explain the chemical composition of the three fingers in the NE jet. We also detect significant differences in the physical and chemical properties among the three fingers analyzed of the NE jet. In particular, we find that, unlike the other two, the southernmost finger originated from a slightly more peripheral region of the explosion. Moreover, while the northern and central fingers lie almost in the plane of the sky, the southernmost finger is moving in a different direction, showing a velocity along the line of sight of ∼2100 km s ^−1 toward the observer, with a tilt angle of ∼16°. These findings highlight the NE jet’s role in ejecting material from the deepest explosive burning layers, providing new insights into the asymmetries originating in the inner layers of CCSNe.